FUTURE-READY TEACHING: DEVELOPING CORE SKILLS OF DOUBLE-QUALIFIED TEACHERS IN VOCATIONAL EDUCATION - Tao , Li Jun; Min, Wang Hui (Research Journal of Education and Allied Studies, 2024)
The development of core quality in "doublequalified" teachers is a continuous and essential process for vocational colleges. Recognizing the significance of this development in accordance with their unique circumstances and growth requirements is imperative for institutions. Emphasis should be placed on enhancing the quality and effectiveness of training, particularly for teachers' areas of weakness. Additionally, education authorities should establish consistent and comprehensive training standards to promote the standardization of core quality advancement for "doublequalified" teachers.